ANALYSIS OF FINANCIAL REPORT INTEGRITY IN GOVERNMENT COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Husaini; Nurhasanah; Tista Febriani; Dinda Mutiara (RADJA PUBLIKA, 2025)
This study aims to analyse the integrity of financial reports in government companies in Indonesia. The independent variables examined in this research include independent commissioners, intellectual capital, audit committees, and audit tenure. The population comprises all of government companies listed on the Indonesia Stock Exchange during the period 2021–2023. Using purposive sampling, 20 companies were selected, resulting in a total of 60 observations analysed through panel data regression. Data analysis was conducted using EViews 12. The results indicate that the presence of independent commissioners has a positive and significant impact on financial report integrity. In contrast, intellectual capital shows a negative and significant influence. Meanwhile, the audit committee and audit tenure variables do not have a significant effect. The findings of this study are expected to assist potential investors in evaluating the quality of financial reporting as part of their decision-making process.